(untitled) (Third Sector Social Economic Review, 2020)
The high production and export potential of enterprises with high technology intensity is also important for the country’s economy. Especially, it is seen that the majority of the enterprises operating in Technoparks established under universities are high-density technology companies. These businesses produce goods and exports of services in the process of becoming closure of Turkey’s foreign trade deficit is of great importance at a serious level. Where these enterprises are in the existing literature in entering foreign markets is a subject that has been investigated. The starting points of such enterprises in the internationalization process and how they continue the process are the main subject of this research.